Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises: 12

Answer

$x=\frac{-1±\sqrt (1+8e^{2})}{4}$

Work Step by Step

Given: $ln(2x+1)=2-lnx$ $(2x+1)=e^{2-lnx}$ $(2x+1)=\frac{e^{2}}{x}$ $2x^{2}+x-e^{2}=0$ This implies $x=\frac{-1±\sqrt (1+8e^{2})}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.